Human Capital Behavior in the Renewable Energy Sector of Nepal - Yadav, Maheshwar Prasad (Nepal Journal of Multidisciplinary Research, 2023)
Purpose: The paper aims at analyzing human capital behavior in the context of the renewable energy sector in Nepal. Design/methodology/approach: The study comprises a descriptive research design based on both primary and secondary data. The required primary data were collected by conducting a field survey using a structured questionnaire on a sample of 118 Nepalese renewable energy enterprises having 264 respondents. Likewise, the secondary data were collected through relevant publications. The collected data were analyzed using simple statistical tools to derive results leading to major findings of the study. Results/findings: The study shows that human capital factors, entrepreneur's education, age, work history, and support networks have positive contributions to business success. The study further reveals that entrepreneurs must be jacks of all trades who need not excel in any one skill but are competent in many. Originality/value: This study is useful for renewable energy entrepreneurs to grow their businesses by focusing on the relevant human capital behavior in the context of the renewable energy sector in Nepal. This work may potentially be useful to academia for future studies. Future avenue: The study can be extended by incorporating the opinion and views of respondents from customers, regulating authorities, and development actors in the sector in future studies.